Error Investigation for Free Form Surfaces in Bezier Techniques - Ahmed A.A. Duroobi; Safaa Kadhim Ghazi; Rasha Ramiz Alyas (Journal of Engineering, 2018)
Surface modeling utilizing Bezier technique is one of the more important tool in computer aided geometric design (CAD). The aim of this work is to design and implement multi-patches Bezier free-form surface. The technique has an effective contribution in technology domains and in ships, aircrafts, and cars industry, moreover for its wide utilization in making the molds. This work is includes the synthesis of these patches in a method that is allow the participation of these control point for the merge of the patches, and the confluence of patches at similar degree sides due to degree variation per patch.  The model has been implemented to represent the surface. The interior data of the desired surfaces designed by MATLAB software have been transformed to UG-NX8 software to get the machining process simulation and G-code programs for the model, as well as a virtual machining process has been simulated to show the machining pitfalls, using CIMCO edit software. The sample has been machined using 3-axis vertical CNC machine. Finally, the sample has been measured using (CMM inspection) and it’s found that the average of error (0.144 mm).